2020
DOI: 10.3390/coatings10080724
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Silt Capillary Water Absorption upon Addition of Sodium Methyl Silicate (SMS) and Microscopic Mechanism Analysis

Abstract: Silt has the characteristics of developed capillary pores and strong water sensitivity, and capillary water is an important factor inducing the erosion and slumping of silt sites. Therefore, in order to suppress the effect of capillary water, this article discusses the improvement effect of sodium methyl silicate (SMS) on silt. The effect was investigated by capillary water rise testing and contact angle measurement, and the inhibition mechanism is discussed from the microscopic view by X-ray diffraction (XRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Sodium methyl silicate is a new type of rigid building waterproof material with good penetrating crystallinity. The silanol group in its molecular structure reacts with the silanol group in the silicate material through dehydration and crosslinking, thereby forming an excellent hydrophobic layer, which has the functions of micro-swelling and increasing compactness [ 15 , 16 ]. Its chemical reaction equation is as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Sodium methyl silicate is a new type of rigid building waterproof material with good penetrating crystallinity. The silanol group in its molecular structure reacts with the silanol group in the silicate material through dehydration and crosslinking, thereby forming an excellent hydrophobic layer, which has the functions of micro-swelling and increasing compactness [ 15 , 16 ]. Its chemical reaction equation is as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Alkali-activated slag containing methylsilicate had a dense microstructure, low water absorption and chloride permeability, because the hydrophobic group (-CH3) from methylsilicate was grafted onto the gel chemical structure through condensation reaction [24]. SMS can also be used to prepare hydrophobic de-icing salts for concrete and inhibit the capillary adsorption properties of silt [39][40]. Although these organic admixtures with hydrophobic modification capacity have the potential to mitigate the early-age shrinkage of geopolymers, there is a lack of systematic study and analysis on their effects and mechanisms, which is of great significance to prevent the early-age cracking and increase the engineering benefits.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a basis for the application and corrosion monitoring of pipeline steel [ 27 , 28 ]. A significant amount of research has also been reported by domestic and international scholars on the effects of capillary action [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Rad and Shokri studied the influence of evaporation from porous media of salt solutions by the interaction between the transport properties of the porous media, the thermodynamics of the evaporating solution, and the environmental conditions [ 41 ].…”
Section: Introductionmentioning
confidence: 99%